Phenylalanine Tolerance over Time in Phenylketonuria - Pinto, Alex (2023)
Funding Information: A.P. received an educational grant from Cambrooke Therapeutics and grants from Vitaflo International, Nutricia, Merck Serono, Biomarin, Mevalia and Applied Pharma Research to attend scientific meetings. This project is also part of A.P’s. PhD, which is funded by Vitaflo International. J.C.R. was a member of the European Nutritionist ExpertPanel (Biomarin), the Advisory Board for Applied Pharma Research, Vitaflo, Synlogic, Biomarin and Nutricia, and received honoraria as speaker from APR, Merck Serono, Biomarin, Nutricia, Vitaflo, Cambrooke, PIAM and Lifediet. A.M. has received research funding and honoraria from Danone Nutricia, Vitaflo International, Biomarin, MetaX, Applied Pharma Research, and Merck Serono; she is a member of the advisory board for Danone Nutricia, Arla, and Applied Pharma Research. The remaining authors declare no conflicts of interest. ® Publisher Copyright: © 2023 by the authors.